Alginate/polycaprolactone composite fibers as multifunctional wound dressings. (1st August 2022) - Hu, Wei-Wen; Lin, Yu-Ting
Abstract: We developed a composite wound dressing that provides multifunctional wound care. Alginate and polycaprolactone (PCL) were coelectrospun as composite fibers. Highly absorbent alginate provided a moist environment for wounds and PCL increased cell adhesion. Silver nanoparticles embedded in PCL fibers for long-term release inhibited the growth of microorganisms. In addition, plasmid DNA encoding platelet-derived growth factor-B (PDGF-B) were complexed with polyethylenimine (PEI) to form cationic nanoparticles which were then adsorbed on anionic alginate fibers through electrostatic interaction. As wound cells adhered to composite fibers, they were in situ transfected to express PDGF-B continuously. Moreover, calcium ions in alginate fibers were released into the wound site through ion exchange to accelerate hemostasis. Wound healing experiments demonstrated that PDGF-B gene-loaded composite fibers accelerated wound closure and promoted collagen formation. We expect this comprehensive study offers an ideal multifunctional solution to facilitate wound healing. Highlights: Alginate and PCL are coelectrospun as composite fibers to preserve their specific properties. Nano-silver loaded PCL fibers inhibit the growth of bacteria. Calcium ions released from crosslinked alginate fibers accelerate blood coagulation. PDGF-B gene-loaded fibers improve wound closure and promote collagen formation. Composite fibers can reduce bacteria, accelerate hemostasis, and promote regeneration.